Day-care expansion and parental subjective well-being: Evidence from Germany - Pia S. Schober; Christian Schmitt (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This study investigates whether the expansion of day-care places for under-three-year-old children in East and West Germany from 2007 to 2011 has improved the subjective wellbeing for mothers and fathers with a youngest child in this age group. We extend existing cross-sectional country comparisons and single country policy evaluations by comparing regional variations over time in two different contexts in terms of work-care ideals, labour market, and child care policies. The empirical analysis links administrative records on daycare use at youth welfare office district level from 2007 to 2011 to regionally aggregated data from the Socio-Economic Panel (SOEP) for 2007 to 2011 and from the 'Families in Germany'-Study (Familien in Deutschland, FID) for 2010 and 2011. We apply fixed-effects models at the county level. We find that in regions with larger day-care growth mothers and fathers expressed greater satisfaction with the available child care. In West Germany, the daycare expansion was positively associated with an increase in maternal satisfaction with family life, health, personal income, and life overall, whereas fathers' subjective well-being was less affected. In East Germany, for mothers the associations with some domains were similarly positive but reached statistical significance only for maternal satisfaction with family life. The results suggest that the excess demand before the expansion in West and East Germany restricted maternal choice and well-being more than fathers'.
Keywords: 330; well-being; satisfaction; parenthood; early childhood education and care; child care